2014
DOI: 10.1017/s0022215114001030
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and its association with psychiatric disorders: systematic review

Abstract: The prevalence of psychiatric disorders, especially anxiety and depression, is high in tinnitus patients, and the presence of these disorders correlates with tinnitus-related annoyance and severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
100
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 27 publications
12
100
0
5
Order By: Relevance
“…Akin to other studies, ours also demonstrates a strong relationship between tinnitus and psychological comorbidities in both genders 27,28 with the greatest differences in tinnitus comorbidities existing in the younger sufferers irrespective of gender. A reduction in the scores for all HRQoL domains is noted in this study like in a previously reported one 29 .…”
Section: Discussionsupporting
confidence: 80%
“…Akin to other studies, ours also demonstrates a strong relationship between tinnitus and psychological comorbidities in both genders 27,28 with the greatest differences in tinnitus comorbidities existing in the younger sufferers irrespective of gender. A reduction in the scores for all HRQoL domains is noted in this study like in a previously reported one 29 .…”
Section: Discussionsupporting
confidence: 80%
“…In addition to chronic insomnia, some published studies with different research methods disclosed scientific evidence of the associations between tinnitus and psychiatric disorders [4][5][6][7][8]. A certain prevalence of numerous comorbid psychiatric disorders have been reported in individuals seeking medical help for tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a systematic review including 16 selected articles demonstrated the occurrence of psychiatric disorders is high in tinnitus patients, especially anxiety and depression. These disorders correlate with tinnitus-related annoyance and severity [5]. A recent survey of 962 adults indicated that about one-third of adolescents experience tinnitus possibly in connection with psycho-emotional factors.…”
Section: Discussionmentioning
confidence: 99%
“…It can be divided into objective and subjective, the first being audible for someone other than the patient (PINTO et al, 2014). Various studies have separately explored the association between high levels of depression and tinnitus (LANGGUTH et al, 2011), and elevated depression and TMD levels (DOHRENWEND et al, 1999;FERNANDES et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The review of 153 articles, done by Pinto (2014) demonstrated a high prevalence of psychiatric disorders in patients affected by tinnitus, reported in fifteen articles. Nine studies showed high correlation between the presence of psychiatric disorders, negative impact on quality of life, and the severity of this otological change.…”
Section: Discussionmentioning
confidence: 99%